Hubungan Aktivitas Fisik Dengan Nyeri Punggung Bawah Saat Pandemi Covid-19 Pada Mahasiswa fakultas Kedokteran - Clara Stephanie Paul; Jimmy Fransisco Abadinta Barus; Ecie Budiyanti; Linda Suryakusuma (PERDOSNI, 2021)
Introduction: COVID-19 pandemic changes lifestyle in society, one of the most obvious changes is physical activity. Physical activity has been known as one of risk factors of low back pain. Aims: To determine the relationship between physical activity and complaints of low back pain during COVID-19 pandemic among students at Faculty of Medicine and Health Science Atma Jaya Catholic University. Methods: A cross-sectional study was conducted in February until March 2021 with the studied respondents were preclinic students of Faculty of Medicine and Health Science Atma Jaya Catholic University. Data were obtained through questionnaires by online with Google Forms. Data were analyzed using Chi-Square test with significant level was set at 0,05. Results: Among 109 respondents, 52,3% medical students had moderate physical activity intensity and 27,5% had low back pain complaints. Bivariate analysis found no association between physical activity and complaints of low back pain during COVID-19 pandemic among medical students (p = 0,547). Discussion: There was no significant association between physical activity and complaints of low back pain. However, it was found that the tendency of low back pain was experienced by students who showed decrease in physical activity during the COVID-19 pandemic. Keywords: physical activity, low back pain, COVID-19 pandemic, medical student